Brachial neuritis following a corticosteroid injection. (4th March 2014) - Robinson, Matthew; Fulcher, Mark
Abstract : This report presents a case of brachial neuritis following a subacromial corticosteroid injection. The patient developed an anterior interosseous neuropathy shortly after the injection, with no other trigger being identified. This neuropathy has unfortunately not shown any sign of recovery at 2 years. The authors propose that corticosteroid injection be added to the list of possible triggering events of brachial neuritis and highlight the frequent use of oral corticosteroids in its treatment. (1) The injection of local anaesthetic and corticosteroid should be considered as a potential trigger for brachial neuritis. (2) Brachial neuritis should be considered in the differential diagnosis for patients presenting with severe arm pain and weakness. (3) The nerves originating from the upper trunk of the brachial plexus are most commonly affected. (4) The anterior interosseous nerve is involved in one-third of cases.